2021
DOI: 10.1155/2021/2548665
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Comparison of MEBO and Hyaluronic Acid Gel in the Management of Pain after Free Gingival Graft Harvesting: A Randomized Clinical Trial

Abstract: Aim. This study aimed to compare the effect of MEBO versus 0.2% hyaluronic acid gel (Gengigel®) applied to the palatal donor site on postoperative pain reduction and wound healing after free gingival graft harvesting. Methodology. Thirty-nine patients with different mucogingival defects were included in this study for harvesting a free gingival graft (FGG) for soft tissue augmentation. Patients were randomly assigned into three equal groups: group I (MEBO), group II (0.2% HA Gengigel®), and group III (control)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…These findings are consistent with the results of a study that reported that HA improved oral wound healing. 24 , 25 However, there were no significant differences in the promotion of wound healing between the HA gel and HA film groups in this study.…”
Section: Discussioncontrasting
confidence: 56%
“…These findings are consistent with the results of a study that reported that HA improved oral wound healing. 24 , 25 However, there were no significant differences in the promotion of wound healing between the HA gel and HA film groups in this study.…”
Section: Discussioncontrasting
confidence: 56%
“…According to the results of the study, there was no difference between the two groups in terms of CM, and pain levels were higher in the control group compared to the HA group in the first seven days [ 44 ]. Hassan et al [ 45 ] compared 0.2% HA gel, MEBO, and the control group, and it was found that the study groups showed significantly lower VAS scores on the 2 nd and 3 rd days compared to the control group. They stated that from the 4th day, the patients did not have any pain although there was no difference between the groups in terms of wound size at any time.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of HA gel on the oral cavity have also been documented in different clinical situations, such as the treatment of chronic periodontitis by the subgingival application after scaling and root planing, with a decrease in inflammation [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%